2019
DOI: 10.1111/jocd.12852
|View full text |Cite
|
Sign up to set email alerts
|

Periorbital pigmentation: An alarming sign of metabolic syndrome

Abstract: Periorbital pigmentation is a commonly encountered condition which presents clinically as bilateral round, oval or semicircular homogenous dark brown pigmented macules in the periocular region. It may influence quality of life of an individual with its strong psychological impact. We present a case of middle-aged female patient, who had periorbital pigmentation as a manifestation of acanthosis nigricans. On evaluation, she was found to have hypertension, hyperglycemia, and dyslipidemia and she fulfilled the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This link appears to start early, and a systematic review demonstrated the relationship between AN and IR/T2DM in children with obesity (Abraham and Rozmus, 2012). Periorbital pigmentation in a female patient with AN was proposed as an alarming sign of MetS (Zawar et al, 2019).…”
Section: Acanthosis Nigricansmentioning
confidence: 99%
“…This link appears to start early, and a systematic review demonstrated the relationship between AN and IR/T2DM in children with obesity (Abraham and Rozmus, 2012). Periorbital pigmentation in a female patient with AN was proposed as an alarming sign of MetS (Zawar et al, 2019).…”
Section: Acanthosis Nigricansmentioning
confidence: 99%
“…In the literature, contradictory findings have been published about the connection between gender and obesity. According to Besra et al [7] and Nayak et al [8], POH is associated with women, whereas Zawar et al [9] found that POH is associated with obesity in women. The limited number of patients included in this research, as well as the fact that the control group was chosen to be age and gender matched, may explain our findings.…”
Section: Discussionmentioning
confidence: 99%